FENOMENA MIGRASI TENAGA KERJA PERTANIAN DANDAMPAKNYA TERHADAP PEMBERDAYAAN PETANI DI PROPINSI JAWA TENGAH - GUNAWAN, Endro (Jurnal Ekonomi dan Pembangunan, 2016)
Migration is one of the factors that influence population growth in a region. Migration reflects the inequality factor of economic growth is heavily influenced by factors of family economic conditions and limited natural resources. The purposes  of this study are : 1). Analyzing the phenomenon of migration of agricultural labor in Central Java province, and 2). Knowing the impact of migration on the empowerment of farmers in Central Java province. The study was conducted in four districts in Central Java: Cilacap, Klaten, Sragen and Pati in 2016. The study used primary data by surveying 160 respondent as a farmers. The results of the study obtained information that in 2016 the total labor force (AK) is working and the number of AK that migration has increased compared to the data in 2010. The number of AK migration most in Klaten district as much as 19.6%. This kind of migration is mostly done by AK in Central Java is the migration of commutation of 54.12%, 26.09% permanent migration and migration of circulating 17.39%. The high rate of migration is an indication of the need for empowerment of farmers in the countryside. The mobility of labor from agriculture to non-agriculture sector followed by high urbanization demonstrated by the high growth of the urban population. There are two factors that cause migration, namely the driving factors and pull factors. The economic factor is a dominant factor causes of migration. To reduce the rate of migration should be pursued community empowerment programs directly related to farming in the countryside, so as to create new jobs.